2022
DOI: 10.3389/fmed.2022.916602
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation among individuals experiencing homelessness and traumatic brain injury: A scoping review

Abstract: Traumatic brain injury (TBI) is disproportionately prevalent among individuals experiencing homelessness. While rehabilitation is critical to facilitating recovery after TBI, there is currently limited information on the extent to which rehabilitation is provided to individuals experiencing homelessness and TBI. If unaddressed, this knowledge gap can perpetuate TBI-related challenges and contribute to a repetitive cycle of TBI and homelessness. This scoping review explored the extent to which rehabilitation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In all, 10 databases were identified in collaboration with an information specialist (JB) and searched for relevant articles using a search strategy including text words and subject headings (e.g., MeSH, Emtree) related to IPV and rehabilitation (see Appendix I). Search terms were informed by previous reviews exploring IPV ( Toccalino et al, 2023 ) or the role of rehabilitation professionals ( Chan, Estrella, Baddeliyanage, et al, 2022 ; Chan, Estrella, Syed, et al, 2022 ). The search strategy was first developed in Medline (see Appendix I) and subsequently translated to the databases.…”
Section: Methodsmentioning
confidence: 99%
“…In all, 10 databases were identified in collaboration with an information specialist (JB) and searched for relevant articles using a search strategy including text words and subject headings (e.g., MeSH, Emtree) related to IPV and rehabilitation (see Appendix I). Search terms were informed by previous reviews exploring IPV ( Toccalino et al, 2023 ) or the role of rehabilitation professionals ( Chan, Estrella, Baddeliyanage, et al, 2022 ; Chan, Estrella, Syed, et al, 2022 ). The search strategy was first developed in Medline (see Appendix I) and subsequently translated to the databases.…”
Section: Methodsmentioning
confidence: 99%
“…The search strategy for this scoping review was informed by previous scoping and systematic reviews (38)(39)(40) and developed in collaboration with an Information Specialist (JB) and team members with research and content expertise in TBI, CJS, and rehabilitation (VC, MJE, AC). The strategy for MEDLINE R ALL (in Ovid, including Epub Ahead of Print, In-Process & Other Non-Indexed Citations, Ovid MEDLINE(R) Daily) database was first developed and subsequently translated to: Embase and Embase Classic (Ovid), Cochrane CENTRAL Register of Clinical Trials (Ovid), CINAHL (EBSCO), APA PsycINFO (Ovid), Applied Social Sciences Index and Abstracts (Proquest), Criminal Justice Abstracts (EBSCO), and Nursing and Allied Health (Proquest).…”
Section: Identifying Relevant Studiesmentioning
confidence: 99%
“…Such intervention plans included psychoeducation on TBI and its consequences; strategies and functional aids to address TBIrelated impairments; and modifications to interventions. The need for screening is not new and has been highlighted in studies that focused on underserved populations with TBI (40,(75)(76)(77)(78)(79). Unfortunately, despite literature supporting the need for TBI screening, almost half of the articles identified in this review did not specify how TBI was ascertained.…”
Section: Opportunities To Integrate Rehabilitationmentioning
confidence: 99%
“…into the rehabilitation needs of people experiencing homelessness has demonstrated high levels of physical limitation, cognitive and functional impairments. A scoping review also demonstrated there are existing programmes of rehabilitation targeting this population with opportunities to further tailor existing services to better meet the needs of people experiencing homelessness [18][19][20][21]. Policy guidance regarding the health of people experiencing homelessness, is clear that identification of brain injury, and management of its sequelae should be priority areas in inclusion health efforts [2,18].…”
Section: Introductionmentioning
confidence: 99%